Adsorptive and photocatalytic removal of reactive dyes by silver nanoparticle-colemanite ore waste - Yola, M.; Eren, T.; Atar, N.; Wang, Shaobin (2013)
A novel composite containing silver nanoparticles (AgNPs) and colemanite ore waste (COW) was synthesized and tested in adsorption and photocatalysis to remove Reactive Yellow 86 (RY86) and Reactive Red 2 (RR2) from aqueous solution in single and binary dye systems. Transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction patterns (XRD) showed the formation of metal AgNPs on COW. The BET surface area increased after intercalation of AgNPs onto COW. Ag-COW was found to be a good material for dye adsorption. The effects of operating variables such as initial dye concentration, pH and contact time in adsorption were studied. The kinetics, isotherm and thermodynamic parameters for the adsorptive removal of the reactive dyes were also investigated. In addition, Ag-COW also shows high photocatalytic activity for degradation of the reactive dyes from single and binary dye solutions. The combination of adsorption and photocatalysis using Ag-COW is demonstrated as a more effective technique for contaminant removal from aqueous solution.